DESIGN OF AUTOMATIC HAND WASHING USING HC-SR04 SENSOR METHOD AND MICROSERVO BASED ON IOT (CASE STUDY: MAGISTER COFFEE) - Bima Sakti Nurdewantoro; Rinna Rachmatika (STIE AUB Surakarta, 2022)
This automatic hand washing tool is one of the tools that helps the community in implementing health protocols in the new normal era as it is today. The current pandemic is caused by the covid 19 virus, which is where the spread of this virus is very fast because the virus can stop at objects. The public is advised to implement health protocols to minimize the spread of the virus, one of which is washing hands. However, public facilities for washing hands still touch objects on the water faucet. So the purpose of this research is to design an automatic hand washing device using sensors. This tool is designed using Arduino Uno hardware and the HC-SR04 sensor as the main component, and several other hardware, assisted by the Internet of Things system to send notifications to find out if someone is using hand washing tools. That way people can carry out the process of washing their hands without touching the object on the water faucet.